Avaliação da qualidade das águas e sedimentos da sub-bacia do rio Barigüi, região Metropolitana de Curitiba-PR - Silva, Paulo Roberto Bairros da (2015)
This study evaluated the water and sediment quality of the Barigui River sub-basin, Greater Curitiba, in terms of the presence, chemical availability, and toxic potential of common chemical species as well as trace elements. Urban basin sediments are complex multi-element environmental matrices and have become the subject of many studies because of their active character. These matrices interchange chemical species with the water column, which affects its quality, influences its toxicity, and interferes with aquatic life. Four sampling operations were completed at three different sites, subject to several environmental impacts due to urbanization and industrialization, in order to cover distinct regions of the sub-basin. For the quantification of chemical species in the sediments and water column, flame-atomizer atomic absorption spectroscopy (FAAS) and energy-dispersive X-ray fluorescence spectroscopy (EDXRF) techniques were used, according to protocol 3030B (APHA), 3050B (USEPA) and 200.2 (USEPA). Auxiliary parameters such as redox potential, pH, ammonia, total phosphorus and orthophosphate, total alkalinity, and chlorophyll a were determined for the water samples. The water samples were also characterized by molecular absorption spectroscopy and molecular fluorescence spectroscopy. The trophic state of the water was established using the trophic state index (TSI) and the determined values were compared with the regulatory values pertaining to CONAMA (2005) resolution 357. The sediments were subjected to thermal analysis (TGA/DSC), particle size and moisture content (%) estimation, and geochemical quality index determination. The results allowed us to differentiate between the studied regions and to conclude that the water and sediment samples are influenced by urbanization and industrialization, which are the main agents responsible for pollution. In this context, the Araucária sample was more degraded than those in Almirante Tamandaré and Santa Felicidade in the Barigui River sub-basin – PR, indicating the need for environmental management in this water system.